The Mechanisation and Automation of the IBS Construction Approach in Malaysia - Siti Syariazulfa, Kamaruddin; Mohammad Fadhil, Mohammad; Rohana, Mahbub; Khairani, Ahmad (e-International Publishing House, 2018)
The objective of the main research is to investigate the current state of implementation of mechanisation and automation in the Industrialised Building System (IBS). The aim of this paper however, is to provide an overview on the implementation of mechanisation and automation in the IBS construction approach. Questionnaire survey and semi structured interviews were conducted to collect the viewpoints among contractors and manufacturers of IBS to ensure the richness of the data collected. The results illustrated that although most respondents have agreed on most critical issues in the implementation of mechanisation and automation, they were not ready to move forward. These responses were quite consistent across the professions. Keywords: Modern method of construction (MMC); industrialised building system (IBS); mechanisation and automation; environment.